Food & Culture: Possible dialogues in times of isolation - Santa Clara Viana Junior, Fernando; Onorato Braga, Lucas; da Silva Merlo, Patrícia Maria (Guará Journal, 2022)
Due to the social isolation caused by the COVID-19 pandemic, social media has become the primary means of consuming information. Thus, we sought to expand our connection with the academic community and society at large through the interface between Food and Culture and the symbolic aspects associated with food during social isolation. Here, through the experience-based method, we will seek to highlight how we operated during the project. Through weekly live streams, based on the personal profiles of the project team members, we addressed a series of ingredients and food practices embedded in people’s daily consumption, addressing their historical trajectories and the meanings of their uses in contemporary times. In total, an estimated audience of 5,000 people viewed the dialogues, which were available on the panelists’ profiles. They were able to reflect on food practices from a historical perspective and rethink current consumption patterns, the meanings implied in food, as well as the return to the kitchen as part of coping with the pandemic itself.